Developing survey-based measures of gendered freedom of movement for use in studies of agricultural value chains - Heckert, Jessica; Myers, Emily; Malapit, Hazel J. (International Food Policy Research Institute, 2020)
Freedom of movement is an important aspect of women’s empowerment, especially in the context of rural transformation as women attempt to transition from subsistence agriculture into more remunerative roles, such as involvement in higher nodes of the agricultural value chain, which often involves marketing activities and traveling away from the home. Nevertheless, there is no agreement on how to measure freedom of movement in large-scale surveys. First, we develop a conceptual framework for studying gendered freedom of movement that considers individual and household characteristics, along with the broader social environment. We then synthesize the existing literature on factors that affect freedom of movement. Next, we review approaches for measuring freedom of movement that have been used in previous surveys. In comparing existing survey-based approaches to the conceptual framework and existing literature, we conclude that existing approaches are limited in several ways. Foremost, they primarily focus on family- and household-based barriers to freedom of movement, and do not consider the barriers present in the broader social environment. Additionally, they lack consideration for how freedom of movement may affect women’s economic participation. To address the need for survey-based modules for studies that examine how freedom of movement is related to economic participation, we propose two new approaches. The first approach is an experience-based module that asks about frequency of visiting specific places, whether they were ever prevented from going to each of these places, and various limiting factors. The second approach uses vignettes designed to understand the relative strength of different social norms limiting women’s freedom of movement and the strength of sanctions that would be imposed for violating these norms. Data collected with these modules have the potential to better understand limitations on women’s freedom of movement and their consequences.